2010
DOI: 10.1016/j.ijid.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment of latent tuberculosis infection in a clinical population in New York City

Abstract: Shorter regimen and DOPT increased completion rates for LTBI. Though efforts to improve TLTBI completion need to address all groups, greater focus is needed for persons who are contacts and HIV-infected, as they have higher risk of developing TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
5
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 23 publications
5
81
5
5
Order By: Relevance
“…Treatment adherence in this study reached 97.7%, which was greater than the adherence rates reported in other studies (e.g., 87.7% and 44%) 47,48 .…”
Section: Discussioncontrasting
confidence: 79%
“…Treatment adherence in this study reached 97.7%, which was greater than the adherence rates reported in other studies (e.g., 87.7% and 44%) 47,48 .…”
Section: Discussioncontrasting
confidence: 79%
“…Alternatively, since the majority of Ugandan youth are unemployed, 17 their less stable economic situation might result in their being unable to meet travel and other costs associated with IPT. [18][19][20][21] Having no education or attaining only primary education was associated with a higher risk of LTFU. An earlier study by Wandwalo and Mørkve demonstrated significant differences in knowledge on TB disease and treatment according to the number of years of school education in Mwanza, Tanzania and its association with poor adherence and LTFU.…”
Section: Discussionmentioning
confidence: 94%
“…Screening uptake and LTBI treatment completion both appear to be suboptimal in real world conditions, despite the high risk of TB in HIV-infected individuals. 9,10 Interferon gamma release assays (IGRAs) could potentially be used to improve screening uptake, as IGRAs can be drawn with other routine bloodwork after HIV diagnosis, and they do not require a 48-72 hour return visit for reading. 6 However, IGRAs present their own challenges, including a lack of long-term followup data in HIV-infected populations, and high rates of conversion and reversion on serial testing.…”
Section: Discussionmentioning
confidence: 99%